Pendampingan Sistem Monitoring Absensi dan Pelanggaran Siswa Berbasis WEB dan BOT Telegram - Mochammad Faid; Mohammad Sa’id; Basori Alwi; Shelly Oktavianti; Muhammad Supyan (GUYUB: Journal of Community Engagement, 2021)
The purpose of this web-based student attendance and student violation information system assistance and telegram bot is to make it easier for schools and student guardians to monitor disciplinary and student violation levels, so that the school can use it in this case SMP Nurul Jadid as evaluation material and consideration for making an Existing policies and regulations at Nurul Jadid Middle School, Telegram Bot are functioned to attend students by the teacher, so that the results of teacher input will be immediately recapitulated by the system, while for the website it is made using the CodeIgniter Framework to facilitate recording related attendance and student violations , while the mentoring process is carried out to the discipline and student affairs department so that later it will be disseminated to all teachers at Nurul Jadid Middle School.